Revolutions In Antibodies Against Influenza Virus - Kaminski, Denise A.; Lee, F. Eun-Hyung (Frontiers in Immunology, 2011)
High-performance neutralizing antibody against influenza virus typically recognizes the globular head region of its hemagglutinin (HA) envelope glycoprotein. To date, approved human vaccination strategies have assumed a divine-right of such antibodies as a sole means of preventing the consequences of this infection. However, frequent amino-acid changes in the HA globular head allow for efficient immune evasion. Consequently, vaccines inducing such neutralizing antibodies need to be annually re-designed and re-administered at a great expense. These vaccines furthermore provide little-to-no immunity against antigenic-shift strains, which arise from complete replacement of HA or of neuraminidase genes, and pose pandemic risks. To address these issues, laboratory research has focused on inducing immunity effective against all strains, regardless of changes in the HA globular head. Despite prior dogma that such cross-protection needs to be induced by cellular immunity alone, several advances in recent years demonstrate that antibodies of other specificities are capable of cross-strain protection in mice. This review discusses the reactivity, induction, efficacy, and mechanisms of antibodies that react with poorly accessible epitopes in the HA stalk, with the matrix 2 membrane ion channel, and even with the internal nucleoprotein. These advances warrant further investigation of the inducibility and efficacy of such revolutionary antibody strategies in humans.